Identifying the Effect of Nuanxin Capsules on Myocardial Injury Induced by Chronic Hypoxia via Network Pharmacology Analysis and Experimental Validation. (4th October 2022) - Mai, Zhexing; Fan, Ye; Ma, Jin; Lou, Tiantian; Ma, Shiyu; Zou, Xu
Abstract : Nuanxin capsule (NX), an in-hospital preparation of Guangdong Provincial Hospital of Chinese Medicine, has been used in heart failure (HF) treatment for 15 years, but its mechanism and protective effect have not been investigated. This study was aimed at exploring the mechanism and protective effect of NX on HF treatment via network pharmacology analysis and experimental validation. Network pharmacology analysis predicted that NX was involved in the regulation of response to apoptotic process and hypoxia via protecting cellular damage and mitochondrial dysfunction against chronic hypoxia. Its mechanism may be involved in the regulation of the PI3K-Akt signaling pathway, HIF-1 signaling pathway, AMPK signaling pathway, and MAPK signaling pathway. Experimental validation indicated that NX was capable of improving cellular viability, restoring cellular morphology, and suppressing cellular apoptosis cellular. NX also exerted cardioprotection by inhibiting mitochondrial membrane potential injury and protecting mitochondrial respiratory and energy metabolism in a chronic hypoxia cellular model, which was consistent with the results of network pharmacology prediction. In addition, the screened active compounds of NX did have a good binding with their key targets, indicating NX may exert protective effect through multicompounds and multitargets. In conclusion, NX had a protective effect on HF through cellular and mitochondrial protection against chronic hypoxia via multicompounds, multitargets, and multipathways, and its mechanism may be involved in modulating the PI3K-Akt signaling pathway, HIF-1 signaling pathway, AMPK signaling pathway, and MAPK signaling pathway.